Highly sensitive refractive index sensor based on asymmetric spectral response of TiO2 high-contrast grating under LED illumination - Yua Okano; Yuusuke Takashima; Masanobu Haraguchi; Yoshiki Naoi (PLoS ONE, 2026)
A highly sensitive intensity-interrogation refractive index (RI) sensor with a light-emitting diode (LED) was experimentally implemented via spectrally asymmetric resonance of a high-contrast grating (HCG). Our novel design concept realizes high sensitivity to RI variations by leveraging the asymmetry of the HCG’s resonant spectrum to control its overlap with the light-source spectrum; in contrast, most conventional designs only focus on shifting the resonant spectrum. Electromagnetic field numerical simulations clarified that an optimized HCG exhibited spectrally asymmetric resonant reflection. The measured reflection spectra showed good agreement with the calculation results, and the reflected light intensity from the sample varied dramatically with a minuscule RI variation under 490 nm LED illumination owing to a significant change in the overlap. An RI sensitivity of 481% per refractive index unit (RIU) and an RI limit of detection of 9.98 × 10 −4 RIU were experimentally achieved. Our sensor can be used in a wide range of applications owing to its high RI sensitivity and simple LED-based system without complex equipment, such as a spectrometer or angle-resolved setup.